KAJIAN PELAKSANAAN PRAKTIK PENGALAMAN LAPANGAN (PPL) MAHASISWA FAKULTAS ILMU TARBIYAH DAN KEGURUAN IAIN WALISONGO SEMARANG - Hashona, Achmad Hasmi (IAIN Ponorogo, 2014)
Abstract: FieldExperience Practice (PPL) is programmed activity to student as educator candidate in school activity both in and outside class. PPL as sharpen media to studentteaching ability, in order to apply science which have been obtained bylearning in the education program. In line with target of education, Faculty Science of Tarbiyah and Teacher ship, representing one of the faculty in IAIN Walisongo Semarangenvironment, aim to develop competence and improve professionalism in the field of Islamic Education, which consist of Education Of Islamic Religion (PAI), Education Of Language Arab (PBA), Islamic Education (KI) and Tadris MIPA (Education Of Mathematics, Education Of Biology, Education Of Chemistry, Education of Physics and Education of English).This solution focused to study execution of PPL in Faculty Science of Tarbiyah and Teacher ship of IAIN Walisongo Semarang which practice at Madrasa and expected can give idea contribution and policy to improve and repair pattern of PPL with good quality and give many benefit not only for student of practical, but also for the Institute and progress of education itself.Â Ø§ÙØªØ¹ÙÙÙ Ø£ÙØ´Ø·Ø© ÙÙ Ø§ÙÙ ØØªÙ ÙÙÙ ÙÙ Ø¹ÙÙ ÙÙ ÙÙØ·ÙØ§Ø¨ Ø§ÙÙ Ø¨Ø±Ù Ø¬Ø© Ø§ÙØ£ÙØ´Ø·Ø© Ù Ù Ø³ÙØ³ÙØ© Ø¹Ù Ø¹Ø¨Ø§Ø±Ø© )PPL( ÙÙ Ø§ÙÙ Ù Ø§Ø±Ø³Ø© ØªØ¬Ø±Ø¨Ø©Â ÙØ±Ø®Ø£ Ø©Ø±Ø§Ø¨Ø¹Ø¨Ù ØØ§ÙØªØ¯Ø±ÙØ³ Ù Ù Ø§Ø±Ø³Ø©Â ÙÙ ÙØ¯Ø±Ø§ØªÙÙ Â ÙÙØµÙÂ ÙÙØ·ÙØ§Ø¨ ÙØ³ÙÙØ©Â PPL ÙÙÂ .Ø§ÙØ¯Ø±Ø§Ø³ÙØ©Â Ø§ÙÙØµÙÙÂ ÙØ®Ø§Ø±Ø¬Â Ø¯Ø§Ø®Ù ÙØ§ÙØªØ¹ÙÙ Â ÙØªÙ Ø´ÙØ§Â .Ø§ÙØªØ¹ÙÙÙ ÙØ©Â Ø§ÙØ¨Ø±Ø§Ù Ø¬Â ÙÙÂ Ø¥ÙØ²Ø§Ù ÙØ©Â ÙÙ Ø§Ø¯Ø©Â Ù Ù Ø§Ø±Ø³Ø©Â Ø³ÙØ¨ Ø§ÙÙÙÙØ©Â ÙÙÂ Ø§ÙÙ ØØ§Ø¶Ø±Ø§Øª Ø®ÙØ§ÙÂ Ø§ÙØªØ³Ø§Ø¨ÙØ§Â ØªÙ Â Ø§ÙØªÙ Ø§ÙÙ Ø¹Ø±ÙØ©Â ÙØªØ·Ø¨ÙÙÂ ÙØ¥Ø¹Ø¯Ø§Ø¯Â ÙØ¯ÙÙ ÙØ°ÙØ§Ù ØÙÙÂ Walisongo IAIN Ø³ÙÙ Ø§Ø±Ø§ÙØ¬ Ø§ÙÙÙÙØ§Øª Ù Ù ÙØ§ØØ¯Ø©Â ÙÙ ØÙØ§ÙØªØ¹ÙÙÙ Â Ø©ÙÙÙ ØØ§ÙØªØ±Ø¨ÙØ©Â Ø£ÙØ¯Ø§Ù Ù Ø¹Â )Ø§Ø¨Ø¨)Â Ø§ÙØªØ¹ÙÙÙ Â Ø©ÙØ¨Ø±Ø¹ÙØ§ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ©Â Ø§ÙØªØ±Ø¨ÙØ©Â Ù ÙÂ ØªØªØ£ÙÙ Ø§ÙØªÙ ØØ§ÙØ¥Ø³ÙØ§Ù Ù Ø§ÙØªØ¹ÙÙÙ Â Ù Ø¬Ø§ÙÂ ÙÙ ÙØ§ØªØ±ØÙØ§Ø§ÙÂ Ø§ÙÙÙØ§Ø¡Ø©Â Ø²ÙØ²Ø¹ØªÙÂ Ø§ÙØ®Ø¨Ø±Ø§Ø¡Â ÙØ§ÙØ¥ÙØ¬ÙÙØ²ÙØ©Â Ø©ÙÙØ¯Ø¨ÙØ§ Ø©ÙØ¨ØªØ±ÙØ§Ù ØØ§ÙØªØ¹ÙÙÙ Â Ø¡Ø§ÙÙ ÙÙÙØ§ ØØ§ÙØ£ØÙØ§Ø¡Â Ø¹ÙÙ Â ÙØ§ÙØªØ¹ÙÙÙ Â Ø§ÙØªØ±Ø¨ÙØ©Â )Ø§ÙØ±ÙØ§Ø¶ÙØ§Øª ÙØ§ÙØ±ÙØ§Ø¶ÙØ§Øª Ø§ÙØ¥Ø³ÙØ§Ù ÙØ©Â Ø§ÙØªØ±Ø¨ÙØ©Â Ù Ù Ø§Ø±Ø³Ø© ÙÙ IAIN Walisongo ØªØ¹Ù ÙÂ ÙÙÙØ© ÙØ§ÙØªØ¹ÙÙÙ Â ÙØ·Ø§Ù PPL ÙÙÂ ØªÙÙÙØ° ØªÙÙÙÙ Ø¹ÙÙ Ø§ÙÙ ÙØ§ÙØ´Ø© ÙØ°Ù Ø§ÙØªØ¹ÙÙÙ (. ÙØªØ±ÙØ²Â ÙÙØ³ Ø§ÙÙÙØ§Ø¦Ø¯Â Ù Ù Ø§ÙØ¹Ø¯ÙØ¯Â ÙØªÙÙÙØ± Ø£ÙÙ Ø§Ø· ÙÙØ¹ÙØ©Â ÙÙØ³ØªØ ÙÙØ¥ Ø©ÙÙ Ø§Ø±ÙØ§ ØªØ§Ø³Ø§ÙØ³ÙØ§ÙÂ Ø§ÙØ£ÙÙØ§Ø±Â ØªØ³ÙÙ Â ÙØ£ Ø¹ÙÙØªÙÙÂ Ø§ÙØ¯ÙÙÙØ©Â Ø§ÙÙ Ø¯Ø§Ø±Ø³.Ø¨Ø§ÙØªØ¹ÙÙÙ Â Ø§ÙÙÙÙØ¶ ÙÂ ÙÙÙ Ø¹ÙØ¯Â ÙÙÙÙ ØØ·Ø§ÙØ¨ Ø³Ø±Ø§Ù Ù Ù ÙÙØ·